2005
DOI: 10.1097/01.gco.0000175356.25932.c0
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial ablation for heavy menstrual bleeding

Abstract: Both REA and NREA provide at least short- to intermediate-term options to hysterectomy for patients with heavy menstrual bleeding and normal or near-normal endometrial cavities. Consequently, the ideal candidates are likely those who are within 5 years of menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
(75 reference statements)
0
3
0
2
Order By: Relevance
“…The coexistence of other gynaecological pathology, such as adenomyosis or myomas, is associated with increased failure rates. The most important effect is that of age: women over the age of 45 are least likely to need further surgery after endometrial ablation and are probably the ideal candidates for this approach 52 …”
Section: Factors Affecting the Success Of Endometrial Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…The coexistence of other gynaecological pathology, such as adenomyosis or myomas, is associated with increased failure rates. The most important effect is that of age: women over the age of 45 are least likely to need further surgery after endometrial ablation and are probably the ideal candidates for this approach 52 …”
Section: Factors Affecting the Success Of Endometrial Ablationmentioning
confidence: 99%
“…The most important effect is that of age: women over the age of 45 are least likely to need further surgery after endometrial ablation and are probably the ideal candidates for this approach. 52 Cost implications for the National Health Service NICE 53 estimates that if all hysterectomies were to be replaced by endometrial ablation using secondgeneration devices, the NHS would save £32 million per year. NICE concedes that this assumption is simplistic, as some women will invariably need or prefer hysterectomy.…”
Section: Factors Affecting the Success Of Endometrial Ablationmentioning
confidence: 99%
“…7,12 Factores que pueden afectar los resultados de la ablación endometrial Las mujeres mayores de 45 años parecen ser menos propensas a una histerectomía posterior y es más probable conseguir la amenorrea y un resultado satisfactorio que en las menores de 45 años. 26,27 La experiencia y/o la habilidad del cirujano también son consideradas importantes en el resultado de la cirugía. Se ha descrito que la tasa de histerectomía posterior a la ablación puede ser de 12,6%, cuando la resección endometrial es llevada a cabo por un cirujano experimentado, en comparación con el 38% si la totalidad o parte del procedimiento no es realizado por el experto.…”
Section: Complicacionesunclassified
“…Another group [46] compared clinical outcomes and quality of life questionnaires between three second-generation techniques and laser ablation in a descriptive cohort study. The reader may also seek additional information on first-generation ablation devices from a recent review on the subject [48 ]. A recent systematic review [47 ] assessed MEA with Thermachoice 1, and concluded that as no head-to-head trials have been performed between the two techniques, there was not enough evidence of differences in terms of clinical effectiveness to recommend one over another.…”
Section: Comparisons Between Techniquesmentioning
confidence: 99%